Transport and acclimation conditions for the use of an estuarine fish (Pomatoschistus microps) in ecotoxicity bioassays: Effects on enzymatic biomarkers - Quintaneiro, C.
Acclimation of organisms for ecotoxicity testing is in general processed according to Organisation for Economic Co-operation and Development (OECD) and/or Environmental Protection Agency (EPA) guidelines, under controlled conditions. However, when organisms are collected in the field, their capture, transport and adaptation to laboratory conditions are factors of stress. Ill their natural habitat, estuarine fish are exposed to considerable fluctuations of environmental variables, while in laboratory they are acclimated to constant conditions and this can be per se a factor of stress that may influence biomarker responses. Therefore, it is important to investigate the effects of these procedures on estuarine fish performance before using them as test organisms in ecotoxicity bioassays. The goal of the present study was to investigate the effects of transporting the common goby, Pomatoschistus microps from the field (natural populations) to the laboratory and of its acclimation to laboratory conditions on the enzymes acetylcholinesterase (AChE), lactate dehydrogenase (LDH) and glutathione S-transferases (GSTs). Fish were collected in a reference site of the Minho River estuary (NW of Portugal) and the activities of the biomarkers were monitored before and after the transport of organisms to the laboratory and during the acclimation period (at 5, 10 and 15 days). The activities of all the enzymes indicated that capture and transport conditions had no effects on enzymatic activities. Furthermore, AChE, LDH and GST presented higher activities at the end of the acclimation period than at beginning, suggesting a physiological adaptation to laboratory conditions. This adaptation should be taken into consideration ill the experimental design to avoid bias in the interpretation of effects of xenobiotics on biomarkers. (c) 2008 Elsevier Ltd. All rights reserved.